Extraction of Natural Product from Plant Source from Cassia Glauca - Pramod Kumar Singh; Pushkar Pratap Tiwari (International Journal for Research in Applied Sciences and Biotechnology, 2022)
Having D-galacto-D-mannan constitute in structure and in molar ratio of 1:2, a new polysaccharide has been isolated from ripe seeds of Cassia glauca1 Hydorlysis of methylated polysaccharide gave 2,3,4,6 tetra O methyl-D-galactose, 2,3 di- O methyl-D mannose and 2,3,6, tri-O- methyl D- mannose in the molar ratio of 1:1:1 respectively. Both periodate oxidation and methylation studies indicated 32.84% of end group. This shows similarity with the structure of polysaccharide obtained from Guar gum. The above findings together with date of oligosaccharide formed on partial acid catalysed hydrolysis showed the galacto-mannan to consist of a linear chain (14) linked-ß- mannopyranosyl residues some of which are substituted at 6 positions by galactopyranosyl unit, glycosidically. This polysaccharide in non-ionic in nature & having presence of D-glactose in the peripheral position.